2011
DOI: 10.1105/tpc.110.081950
|View full text |Cite
|
Sign up to set email alerts
|

β-Amylase–Like Proteins Function as Transcription Factors in Arabidopsis, Controlling Shoot Growth and Development    

Abstract: Plants contain b-amylase-like proteins (BAMs; enzymes usually associated with starch breakdown) present in the nucleus rather than targeted to the chloroplast. They possess BRASSINAZOLE RESISTANT1 (BZR1)-type DNA binding domainsalso found in transcription factors mediating brassinosteroid (BR) responses. The two Arabidopsis thaliana BZR1-BAM proteins (BAM7 and BAM8) bind a cis-regulatory element that both contains a G box and resembles a BR-responsive element. In protoplast transactivation assays, these BZR1-B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
127
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 96 publications
(132 citation statements)
references
References 52 publications
4
127
1
Order By: Relevance
“…We previously demonstrated that both BAM7 and BAM8 fulllength proteins can bind to the BBRE motif, although transcription factor activity could only be demonstrated for BAM8 (Reinhold et al, 2011). We reasoned that this difference might lie in the enzyme-like domains.…”
Section: The Enzyme-like Domains Of Bam7 and Bam8 Have Distinct Functmentioning
confidence: 97%
See 4 more Smart Citations
“…We previously demonstrated that both BAM7 and BAM8 fulllength proteins can bind to the BBRE motif, although transcription factor activity could only be demonstrated for BAM8 (Reinhold et al, 2011). We reasoned that this difference might lie in the enzyme-like domains.…”
Section: The Enzyme-like Domains Of Bam7 and Bam8 Have Distinct Functmentioning
confidence: 97%
“…However, only BAM8 was shown to substantially activate gene transcription via the BBRE motif in protoplasts and transgenic plants (Reinhold et al, 2011). We mined the published genome data of 33 vascular plants, two mosses, and six algae in Phytozome v9.1 (http://www.phytozome.net/) for the presence of BZR1-BAM isoforms.…”
Section: Two Distinct Bzr1-bam Isoforms Are Conserved In Vascular Plantsmentioning
confidence: 99%
See 3 more Smart Citations